Video-based categorization system and frequency analysis of gestures in saxophone playing - Moura, Nádia (2024)
The study of gestures in music performance provides valuable insights for instrumental learning. However, gestural vocabularies vary depending on the instrument being played, according to its postural and technical specificities. The goals of this study were twofold: first, to create a gesture categorization system for saxophone players, and second, to analyse their gestural behaviour across contrasting musical excerpts. A criteria-based observational analysis was conducted, considering the type and frequency of gestures identified in a database of 100 video and motion recordings. The categorization system, including 15 gesture types applicable to the case of saxophone playing, was further validated by 2 expert raters. A descriptive appendix is provided for the identification of each gesture type. Results revealed that: (1) knee and trunk flexion, feet elevation, mediolateral sway and flap were the most recurrent gestures among saxophone players; (2) energetic, fast-tempo excerpts led to higher movement frequency; and (3) impulsive gestures (head nods) were idiosyncratic of the excerpt containing repeated accentuated notes. These results present a definition of the gestural behaviour of saxophone players, which constitutes relevant knowledge for the development of future studies in the fields of injury prevention, body expression and historically informed performance.